(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The general objective of this research work was to contribute to the environment decontamination. Its specific objective to develops sustainable roofing tiles from ecological point of view. In this way this technology contribute in the decontainmenation of the environment since it uses waste material that are burned in municipal land without any use , or accumulated and burned in landfill, causing pollution plastic and rubber are non-biodegradable material so nature cannot absorb them as other waste. The typical tiles made from soil or clay will be limited because it destroyed the farmland on the other land the old and tire and plastic increases year and year which brings serious environmental problem so the plastic tiles made from waste plastic will lot to decrease above environmental pressure. The measurement of physical and mechanical properties show that plastic waste tiles whose proportion in plastic 40give better result than micro-concrete tiles.